2020
DOI: 10.1051/0004-6361/201936938
|View full text |Cite
|
Sign up to set email alerts
|

Wave heating of the solar atmosphere without shocks

Abstract: Context. We investigate the wave heating problem of a solar quiet region and present its plausible solution without involving shock formation. Aims. We aim to use numerical simulations to study wave propagation and dissipation in the partially ionized solar atmosphere, whose model includes both neutrals and ions. Methods. We used a 2.5D two-fluid model of the solar atmosphere to study the wave generation and propagation. The source of these waves is the solar convection located beneath the photosphere. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…The one-dimensional numerical simulations are performed with the JOANNA code (Wójcik et al 2020b), which solves the above-mentioned two-fluid equations. We assume that the system has a slab geometry and that it is invariant along the xand z-directions (∂/∂x = ∂/∂z = 0), and the z−components of the velocities and the magnetic field are set identically zero (V iz = V nz = B z = 0).…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The one-dimensional numerical simulations are performed with the JOANNA code (Wójcik et al 2020b), which solves the above-mentioned two-fluid equations. We assume that the system has a slab geometry and that it is invariant along the xand z-directions (∂/∂x = ∂/∂z = 0), and the z−components of the velocities and the magnetic field are set identically zero (V iz = V nz = B z = 0).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In this paper we considered two-fluid ion magnetoacoustic and neutral acoustic waves that are initially (at t = 0 s) excited by a pulse in a vertical component of the ion and neutral velocities. The full set of two-fluid equations is solved by the JOANNA code (Wójcik et al 2020b). The results of the numerical simulations presented in this paper can be summarised as follows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Soler et al (2019), using a photospheric broadband driver that contains a spectrum of frequencies corresponding to wave periods ranging from 3.33 s up to 2.78 h, in- and Kuźma et al (2020) revealed a rise of the plasma temperature in the solar atmosphere resulting from the collisional heating. The two-fluid effects also play an important role when non-linear effects become important, particularly in the context of wave damping and plasma heating (e.g., Kuźma et al 2019;Wójcik et al 2020;Zhang et al 2021). On top of that, Murawski et al (2020) demonstrated that ion-neutral collisions may solely solve the heating problem of a quiet region of the chromosphere.…”
mentioning
confidence: 99%
“…( 19) is injected into the simulation domain specified as (−0.08, 0.08) × (−0.5, 60) Mm 2 . We use the JOANNA code (Wójcik et al 2020) to perform the numerical simulations, i.e. to solve the two-fluid equations presented and discussed in the previous section.…”
Section: Numerical Resultsmentioning
confidence: 99%